GRASP and IPCEF Promote ARF-to-Rac Signaling and Cell Migration by Coordinating the Association of ARNO/cytohesin 2 with Dock180 - White, David T.; McShea, Katie M.; Attar, Myriam A.; Santy, Lorraine C. (Molecular biology of the cell, 2010)
ARFs are small GTPases that regulate vesicular trafficking, cell shape, and movement. ARFs are subject to extensive regulation by a large number of accessory proteins. The many different accessory proteins are likely specialized to regulate ARF signaling during particular processes. ARNO/cytohesin 2 is an ARF-activating protein that promotes cell migration and cell shape changes. We report here that protein–protein interactions mediated by the coiled-coil domain of ARNO are required for ARNO induced motility. ARNO lacking the coiled-coil domain does not promote migration and does not induce ARF-dependent Rac activation. We find that the coiled-coil domain promotes the assembly of a multiprotein complex containing both ARNO and the Rac-activating protein Dock180. Knockdown of either GRASP/Tamalin or IPCEF, two proteins known to bind to the coiled-coil of ARNO, prevents the association of ARNO and Dock180 and prevents ARNO-induced Rac activation. These data suggest that scaffold proteins can regulate ARF dependent processes by biasing ARF signaling toward particular outputs.